ANALISIS KETERAMPILAN BERPIKIR TINGKAT TINGGI PADA PEMBELAJARAN TEMATIK DI KELAS IV SD - Agdes Dwika Siahaan; Mahmud Alpusari; M. Jaya Adi Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this research was for identifying and describing: the extent to which the implementation of learning carried out by the teacher leads to high order thinking skills and the extent to which the implementation of the assessment contains indicators of measuring higher level thinking skills. This research was conducted in class IV. The type of this research was a qualitative study with a case study design. The subject in this research was a teacher where the teacher carried out the learning activities and made the questions for the learning assessment. The data were collected using observation, interview, and documentation techniques. Based on the results of the research, it can be concluded that the implementation of learning carried out by the teacher had referred to high level thinking skills with 4C indicators: (1) communication, which was from the beginning of learning activities when the teacher did perceptions; (2) collaborative, which was from each meeting in the form of group discussions; (3) critical thinking and problem solving, in which the teacher directed the students to analyze reading texts; (4) creativity and innovation, in which the teacher gave students freedom to do tasks with their own discussions and languages and also they created dance movement. And the implementation of the questions assessments made was more dominant and it refers to low order thinking skills.Key Words: High Order Thinking Skills, The Implementation of Learning, The implementationof the Assessment